Negotiating memory: funerary commemoration as social change in emancipation-era Barbados. Issue 1 (2nd January 2019) - Cook, Katherine
ABSTRACT: Anglican church commemoration in Barbados is traditionally viewed as reflecting a wholly white, British history; however, beginning in the late eighteenth century, these spaces were circumvented as places of memory for the freed black community. As abolition and emancipation triggered greater integration of previously racially segregated groups on the island, funerary monuments provided the opportunity to negotiate memory, social structure, and community relationships, subverting dominant power hierarchies and tensions stimulated by race, religion, and marginalization. This paper will reconstruct narratives and counter-narratives in burial practice and monument use against the backdrop of abolition and emancipation to contribute to historical and archaeological understandings of historical processes of colonization and decolonization, relevant to Barbados and other colonies dependent on slave labour.